Pharmacokinetics, Tissue Distribution and Excretion of Paeonol and Its Major Metabolites in Rats Provide a Further Insight Into Paeonol Effectiveness - Hu, Xintong; Ding, Liqin; Cao, Shijie; Cheng, Lina; Wang, Kun; Guang, Chenxi; Li, Wei; Koike, Kazuo; Qiu, Feng (Frontiers in Pharmacology, 2020)
Paeonol is a major bioactive ingredient in Moutan Cortex (the root barks of Paeonia suffruticosa Andrews) and exhibited a wide range of bioactivities such as anti-inflammation, anti-oxidation, hypoglycemic effect, analgesic and others. Even though paeonol has been proven to possess significant pharmacological and therapeutic effects, its pharmacokinetic properties are not satisfactory since it has been found to have a rapid clearance in vivo. In the present study, the pharmacokinetics, tissue distribution and excretion of paeonol and its major metabolites were investigated in rats by an efficient and specific UPLC-MS/MS method. The results indicated that paeonol was rapidly absorbed, extensively metabolized, and widely distributed in various tissues without long-term accumulation after oral administration to rats. The major distribution tissues of paeonol and its metabolites were kidney, liver, and heart. Paeonol was able to cross the blood-brain barrier but rapidly decreased after 10 min. The total excretion of four metabolites in urine, bile and feces was approximately 35.0% within 24 h, and the metabolites were mainly excreted through the urine. In addition, the hypoglycemic activities of paeonol and its metabolites were investigated by a glucose uptake assay on TNF-α mediated insulin resistance in 3T3-L1 adipocytes. The results showed that paeonol and its major metabolites displayed hypoglycemic activities. This is the first comprehensive and systematic report on the pharmacokinetics of paeonol and its metabolites. This research provides an important basis for the clinical development and application of active metabolites.